Case report: Two PD-L1 positive unresectable advanced pancreatic carcinoma patients with microsatellite stability achieved R0 resection after PD-1 antibody plus chemotherapy as a successful downstaging therapy: A report of two cases - Shang, Lin; Li, Peng; Fan, Jie; Zhao, Chunning; Niu, Xiangying; Bian, Qitian; Yuan, Zhilin; Kong, Yanlong; Zhu, Tingshun; Xu, Bin; Dong, Jianxin; Xiang, Hongjun (Frontiers in Immunology, 2022)
Background Nonobvious early symptoms are a prominent characteristic of pancreatic cancer, resulting in only 20% of patients having resectable tumors at the time of diagnosis. The optimal management of unresectable advanced pancreatic cancer (UAPC) remains an open research question. In this study, the tumors shrank significantly after PD-1 antibody combined with chemotherapy in two UAPC patients, and both have achieved R0 (pathologically negative margin) resection and survival to date. Case presentation Case 1: A 53-year-old man was diagnosed with pancreatic adenocarcinoma (Stage III). He received six cycles of PD-1 antibody plus chemotherapy as the first-line treatment. The tumor was reduced from 11.8×8.8 cm to “0” (the pancreatic head was normal as shown by enhanced computed tomography, ECT) after preoperative neoadjuvant therapy (PNT) and the adverse effects were tolerable. The patient underwent radical surgery and achieved R0 resection. Case 2: A 43-year-old man diagnosed with pancreatic adenocarcinoma with liver metastasis (Stage IV) received three cycles of PD-1 antibody combined with chemotherapy. The tumor was reduced from 5.2×3.9 cm to 2.4×2.3 cm with no side effects. The patient also underwent radical surgery and achieved R0 resection. Conclusion PD-1 antibody plus a chemotherapy regimen resulted in a surprising curative effect and safety in two patients with UAPC, which may portend an improvement in pancreatic carcinoma treatment. We may have a way for UAPC patients to obtain radical treatment and gain long-term survival. Two PD-L1 positive UAPC patients with microsatellite stability (MSS) enlighten us to have a more comprehensive understanding of the prediction of immunotherapy.